The Drosophila PGC-1α Homolog spargel Modulates the Physiological Effects of Endurance Exercise - Tinkerhess, Martin J.; Healy, Lindsey; Morgan, Matthew; Sujkowski, Alyson; Matthys, Erin; Zheng, Li; Wessells, Robert J. (PLOS ONE, 2012)
Endurance exercise is an inexpensive intervention that is thought to provide substantial protection against several age-related pathologies, as well as inducing acute changes to endurance capacity and metabolism. Recently, it has been established that endurance exercise induces conserved alterations in physiological capacity in the invertebrate Drosophila model. If the genetic factors underlying these exercise-induced physiological alterations are widely conserved, then invertebrate genetic model systems will become a valuable tool for testing of genetic and pharmacological mimetics for endurance training. Here, we assess whether the Drosophila homolog of the vertebrate exercise response gene PGC-1α spargel (srl) is necessary or sufficient to induce exercise-dependent phenotypes. We find that reduction of srl expression levels acutely compromises negative geotaxis ability and reduces exercise-induced improvement in both negative geotaxis and time to exhaustion. Conversely, muscle/heart specific srl overexpression improves negative geotaxis and cardiac performance in unexercised flies. In addition, we find that srl overexpression mimics some, but not all, exercise-induced phenotypes, suggesting that other factors also act in parallel to srl to regulate exercise-induced physiological changes in muscle and heart.